The Effectiveness of Policy Implementation on Forest Rehabilitation and Reclamation EFEKTIVITAS IMPLEMENTASI KEBIJAKAN REHABILITASI DAN REKLAMASI HUTAN - Didid Sulastiyo; Hariadi Kartodihardjo; Sudarsono Soedomo (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
The policy on forest rehabilitation and reclamation have been implemented since 1950, but not effective decrease the extend of the critical forest and land yet. The objective of this research was to formulate option of effectiveness enhancement of forest rehabilitation and reclamation policy implementation. This research applied the theory that developed by Edward III and IDS’s policy process. The policy text (rule in form) of forest rehabilitation and reclamation has not been used effectively to solve the solve the problem on the ground because the lack of sufficient regulation on the pre-condition, maintenance and responsibility in regards to the asset lost, participation, empowerment and transparency. There is divergent in the implementation of forest rehabilitation and reclamation policy. The implementation of policy requires high transaction cost with limited participation and did not legitimate due to ineffective communication, structure of birocracy, disposition/attitude and resources. To increase the effectiveness implementation of policy and institution on forest rehabilitation and reclamation, the goverment have to improve the effectiveness of communication, structure of birocracy, disposition/attitude, and resources. Furthermore, the result of this research also recommends the importance of network development through social movement by using mass-media and social media, which will be usefull to provide pressure on the policy development process by addressing the counter policy narative.Key words: efectiveness, implementation, policy, rehabilitation, reclamation